2013
DOI: 10.5014/ajot.2013.008086
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Based on Ayres Sensory Integration in the Treatment of Retentive Fecal Incontinence in a 3-Year-Old Boy

Abstract: OBJECTIVE. We present the case report of a 3-yr-old boy with retentive fecal incontinence and sensory overresponsivity. Sensory integration theory was used to address the overresponsivity affecting the child's ability to acquire age-appropriate toileting habits. We describe the 7 mo of treatment and 3 mo of follow-up in occupational therapy. METHOD. We analyzed a retrospective chart review of daily defecation log outcome data and parent interview. RESULTS. Notable improvements in acquiring age-appropriate toil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Two studies examined elimination behaviors. They concluded that sensory processing may provide an important contribution to our understanding of incontinence and plans for resolving this daily life challenge (Beaudry Bellefeuille, Schaaf, & Ramos Polo, 2013; Pollock, Metz, & Barabash, 2014).…”
Section: Results (Collate Summarize and Report Findings)mentioning
confidence: 99%
“…Two studies examined elimination behaviors. They concluded that sensory processing may provide an important contribution to our understanding of incontinence and plans for resolving this daily life challenge (Beaudry Bellefeuille, Schaaf, & Ramos Polo, 2013; Pollock, Metz, & Barabash, 2014).…”
Section: Results (Collate Summarize and Report Findings)mentioning
confidence: 99%
“…Through sensory processing based on sensory integration theory for treating fecal incontinence in training children, Bellefeuille et al 15 designed a daily defecation plan for parents following to significantly improve toilet behavior in children. Through parental involvement, Case-Smith and Nastro 2 showed parents’ feelings to have a positive effect.…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with an interdisciplinary team, the therapist and the child's parents could include the child's sensory needs as part of their plan for managing the child's DES. For example, if the child is overresponsive to sensory input, extraneous sensory input in the toileting environment could be minimized, graded and engaging activities could help the child become accustomed to the bathroom environment, and Ayres Sensory Integration Ó could help normalize the child's sensory responses (Bellefeuille, Schaaf, & Polo, 2013). Likewise, if the child is underresponsive to sensory input and has low awareness of the need to void, a schedule of timed toileting may be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical practice, it will be important to investigate sensory-based treatment of DES. Following from the case study by Bellefeuille et al (2013), further studies could determine whether treating both DES and SPD simultaneously could result in improved outcomes.…”
Section: The American Journal Of Occupational Therapymentioning
confidence: 99%